Determining the Sediment Quality of Yağlıdere Stream (Giresun) - Arzu Aydın Uncumusaoğlu; Cengiz Mutlu; İlhami Kayış (Turkish Journal of Agriculture: Food Science and Technology)
Sediments in aquatic systems are often contaminated by various pollutants originating from the sources such as industrial and agricultural discharges, municipal wastewater treatment plants, and storm water. These effects lead to the need to develop sediment quality objectives regarding the protection of aquatic ecosystems and human health. In this study, the sediment samples were collected from five sampling sites and then analyzed in order to identify the concentrations of certain metals (As, Se, Ag, Cd, Na, and K), the levels of pH, conductivity, water content (%) and organic matter (%) in the Yağlıdere Stream. Finally, Geo-accumulation index values calculated based on the estimations regarding the background trace element concentrations suggested the anthropogenic influences in most of the samples. In conclusion, it was observed that K, Na, As, and Se dominantly accumulated in the study area. These metals may have a negative impact on the research area and create an environmental risk.